The effect of preheating temperature on PAH/soot formation in methane/air co-flow flames at elevated pressure. (1st April 2022) - Liu, Peng; Guo, JunJun; Quadarella, Erica; Bennett, Anthony; Gubba, Sreenivasa R.; Saxena, Saumitra; Chatakonda, Obulesu; Kloosterman, Jeffrey W.; He, Xiaoyi; Im, Hong G.; Roberts, William L.
Highlights: The soot, PAH, and OH* concentrations were measured. Soot formation is promoted with higher pressure and preheating. Soot enhancement by preheating is limited at high pressure. Fully-resolved simulations were conducted with different PAH models. Abstract: Preheating technology is widely used to improve the emission or efficiency of combustors, such as diesel engines and gasifiers operating at high pressures. Soot is an unwanted by-product, but its formation is unavoidable in high-pressure diffusion combustion. In this study, the effect of preheating temperature on polycyclic aromatic hydrocarbon (PAH) and soot formation in methane/air co-flow flames was comprehensively investigated in the pressure range of 1–5 bar. The temperature of inlet gas ranges from 295 K to 573 K. The soot, PAH, and OH* concentrations were obtained using planar laser-induced incandescence, planar laser induced fluorescence, and chemiluminescence techniques, respectively. The experimental results reveal that soot and PAH formation is greatly enhanced at higher pressure or with a higher preheating temperature of inlet gas. At a fixed preheating temperature, the peak/integrated soot volume fraction follows a power law with pressure. As pressure increases, the enhancement of soot formation by preheating temperature is suppressed. As the preheating temperature is raised from 295 K to 573 K, the integrated soot volume fraction is increased by 33.7 times at 1.5 bar, but the difference narrows to 2.3 times at 5 bar. OH* signal increases with preheating temperature at 1 bar, but the difference becomes indistinguishable at higher pressure. Further, the experimental results were utilized to evaluate the soot modeling, PAH and soot formation under experimental conditions are examined using four different kinetic mechanisms. While the soot trend along different pressure and preheating temperature is qualitatively captured, the quantitative predictions vary depending on the mechanisms. Specifically, KAUST and Narayanaswamy-Blanquart-Pitsch (NBP) mechanisms overpredict the soot volume fraction while DRL and Appel-Bockhorn-Frenklach (ABF) mechanisms underpredicts the soot volume fraction. In terms of the PAH spatial distribution, only DRL and ABF mechanisms show the ability to capture the experimental observations, that is the peak PAH appears in the flame centerline. The reaction pathway analysis indicates both fuel-pyrolysis chemistry and PAH growth chemistry should be accounted for the discrepancy.